Identical Characteristics of Tai Vernacular Houses in Mong Yawng, Shan State, Myanmar - Arthanit , Kanyarat; Oranratmanee, Rawiwan (NAJUA: History of Architecture and Thai Architecture, 2020)
The Tai in Mong Yawng in Shan State of Myanmar, known as Tai Yawng, are Tai Lue who migrated from Sibson Panna several hundred years ago. They brought the indigenous Tai Lue housing patterns and adopted some local patterns of Tai Yai and Tai Khun as well as some modern influences, resulted in the localized patterns. This study explored the villages and houses in this area which has not been researched extensively. Although unique and well-conserved, they are at risk of changes due to modernization and tourism accessibility to the area. The research focus is on the dynamics of architectural patterns as occurred in Tai vernacular architecture. Altogether four villages and nineteen houses are surveyed. The criteria for the selection of villages under study are ones that its villagers continue the peasant way of life and exist the Tai houses; the houses under study, are chosen from their ages of no less than 15 years whose indigenous Tai housing patterns remain. The field methods were based on observations and interviews with inhabitants, leaders and key persons in the area. The results from the survey reveal some identical Tai Lue housing patterns along with some adopted patterns of Tai Yai and Tai Khun. Some climatic adaptation and changes due to the needs and demands of households are also observable in the architecture, as resulted in unique characteristics of its elements.